2012
DOI: 10.1002/etc.1809
|View full text |Cite
|
Sign up to set email alerts
|

Biomagnification of mercury through the benthic food webs of a temperate estuary: Masan Bay, Korea

Abstract: The authors examined food web magnification factors of total mercury (THg) and methylmercury (MeHg) for the benthic organisms in Masan Bay, a semiclosed, temperate estuary located on the southeastern coast of Korea. For benthic invertebrates, concentrations of THg and MeHg (%MeHg) ranged from 9.57 to 195 and 2.56 to 111 ng/g dry weight (12.2-85.6%), respectively. Benthic fish THg and MeHg (%MeHg) concentrations ranged widely from 10.8 to 618 and 2.90 to 529 ng/g dry weight (22.9-93.9%), respectively. The linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 62 publications
0
19
2
Order By: Relevance
“…These calculations assume that our 25–66μm size fraction is largely autotrophic and the processes of mercury species ad-, ab- and desorption are at equilibrium. These values fall within the range of oceanic BCF values derived from, albeit, a limited number of field studies that enable this calculation ( Table 4 ; [ 26 , 74 , 91 97 ]). Earlier experimental work showed that mercury could enter the marine food chain preferentially as MeHg through adsorption to phytoplankton surfaces and absorption into the cytoplasm [ 68 , 69 , 98 ].…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…These calculations assume that our 25–66μm size fraction is largely autotrophic and the processes of mercury species ad-, ab- and desorption are at equilibrium. These values fall within the range of oceanic BCF values derived from, albeit, a limited number of field studies that enable this calculation ( Table 4 ; [ 26 , 74 , 91 97 ]). Earlier experimental work showed that mercury could enter the marine food chain preferentially as MeHg through adsorption to phytoplankton surfaces and absorption into the cytoplasm [ 68 , 69 , 98 ].…”
Section: Resultsmentioning
confidence: 53%
“…The first attempt to describe mercury biomagnification in a reasonably complete marine food web was done in the arctic in the 1990s with the aid of stable isotopes for trophic interpretations [ 21 ]. There are now several relatively complete marine food-chain studies of mercury bioaccumulation in the arctic [ 21 23 ], but fewer in the subarctic [ 24 ], temperate [ 25 , 26 ], subtropical [ 27 ] and tropical latitudes [ 28 ]. The present study is a descriptive field study in which we cover the transition from phytoplankton to the second and third trophic levels in greater detail than previous studies with the hope of gaining more insight into the transition from predominantly sorption to trophic transfer of mercury.…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that benthic associations may increase biotic Hg concentrations via dietary intake or proximate contact with Hg-contaminated sediments, as reported elsewhere (Storelli et al, 1998; Hosseini et al, 2013). Other studies, however, indicate that pelagic-feeding organisms (depleted δ 13 C signatures) have increased Hg exposure (Chen et al, 2009; Kim et al, 2012). Ultimately, the fate of Hg through feeding pathways depends on the number of trophic steps and consumer's utilization of different prey assemblages (Kim et al, 2012), which likely vary across discrete aquatic ecosystems.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies, however, indicate that pelagic-feeding organisms (depleted δ 13 C signatures) have increased Hg exposure (Chen et al, 2009; Kim et al, 2012). Ultimately, the fate of Hg through feeding pathways depends on the number of trophic steps and consumer's utilization of different prey assemblages (Kim et al, 2012), which likely vary across discrete aquatic ecosystems.…”
Section: Resultsmentioning
confidence: 99%
“…For the biota, approximately 0.2-0.5 g of freeze-dried tissues were digested in 20% KOH overnight in a methanol (w/v) solution at 50°C (Hintelmann and Nguyen, 2005;Kim et al, 2012). The aliquots of the DCM extracts and alkaline digestates were converted to volatile ethylmethyl Hg by reacting with a sodium tetraethylborate solution and were collected on Tenax Ò traps through purging with nitrogen gas.…”
Section: Mmhg Analysismentioning
confidence: 99%